ISSUES REGARDING THE IMPROVEMENT OF THE INDIRECT TAXES MECHANISM (Web of Teachers: Inderscience Research, 2024)
In this article, a comprehensive study of the mechanism of taxation of indirect taxes, a scientific proposal for improving the mechanism of taxation and effective tax administration and practical recommendations are highlighted.